2018
DOI: 10.3389/fmicb.2018.02844
|View full text |Cite
|
Sign up to set email alerts
|

Out in the Cold: Identification of Genomic Regions Associated With Cold Tolerance in the Biocontrol Fungus Clonostachys rosea Through Genome-Wide Association Mapping

Abstract: There is an increasing importance for using biocontrol agents in combating plant diseases sustainably and in the long term. As large scale genomic sequencing becomes economically viable, the impact of single nucleotide polymorphisms (SNPs) on biocontrol-associated phenotypes can be easily studied across entire genomes of fungal populations. Here, we improved a previously reported genome assembly of the biocontrol fungus Clonostachys rosea strain IK726 using the PacBio sequencing platform, which resulted in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 90 publications
1
43
0
Order By: Relevance
“…The higher expression of lysm2 during growth on chitincontaining media hints on a possible function of LYSM2 in protecting C. rosea hyphae against endogenous chitinases secreted during external chitin degradation. This hypothesis gain further support by the fact that lysm2 is located adjacent to the killer toxin-like chitinase gene chiC1 in the C. rosea genome Broberg et al, 2018), and that the transcriptional analyses of lysm2 in this study and chiC1 in a previous study showed that both genes are co-induced in medium containing chitin as the sole carbon source. There are several examples of chitinase genes located physically close to co-regulated LysM protein-encoding genes (Gruber et al, 2011;Martinez et al, 2012), indicating an interrelated function of chitinases and LysM proteins (Gruber and Seidl-Seiboth, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…The higher expression of lysm2 during growth on chitincontaining media hints on a possible function of LYSM2 in protecting C. rosea hyphae against endogenous chitinases secreted during external chitin degradation. This hypothesis gain further support by the fact that lysm2 is located adjacent to the killer toxin-like chitinase gene chiC1 in the C. rosea genome Broberg et al, 2018), and that the transcriptional analyses of lysm2 in this study and chiC1 in a previous study showed that both genes are co-induced in medium containing chitin as the sole carbon source. There are several examples of chitinase genes located physically close to co-regulated LysM protein-encoding genes (Gruber et al, 2011;Martinez et al, 2012), indicating an interrelated function of chitinases and LysM proteins (Gruber and Seidl-Seiboth, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Predicted NRPS proteins were retrieved from the C. rosea IK726 genome sequence (Broberg et al., 2018; Karlsson et al., 2015). Identification of conserved protein modules and features was made using the conserved domain database (CDD) (Marchler‐Bauer et al., 2017) and the simple modular architecture research tool (SMART) (Letunic & Bork, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Abbreviation: n.a., ot annotated. a In comparison with the C. rosea strain IK726 reference genome (Broberg et al, 2018).…”
Section: Strains Culture Conditions and Dna Extractionmentioning
confidence: 99%
“…As part of a large-scale C. rosea genome sequencing initiative (Broberg et al, 2018) Figure S2). However, strains identified as C. rhizophaga clustered in two polyphyletic subgroups in the tef1 tree and the tub sequence-based analysis inferred C. byssicola as a paraphyletic group with respect to C. chloroleuca and C. rhizophaga Figure 2b).…”
Section: Genome Sequencing and Identification Of Clonostachys Strainsmentioning
confidence: 99%